2024
DOI: 10.1039/d3cy01753b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ni content on Cu–Mn/ZrO2 catalysts for methanol synthesis from CO2 hydrogenation

Hengbi Zhang,
Jinhai Yang,
Shiwei Wang
et al.

Abstract: Cu–Mn/ZrO2 catalysts with different Ni contents were used for CO2 hydrogenation to methanol, among which the CMNZ-0.01 catalyst was the most effective, and the addition of Ni made the catalyst more oriented toward the COOH* pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(88 reference statements)
0
1
0
Order By: Relevance
“…Herein, the bimetallic alloy model was constructed by substituting the copper atoms with other transition metal (TM) atoms (Au, Ni, Pd, Pt and Zn). The primary rationale for selecting TM atoms was based on a literature review, which identified Au–Cu, 4,36,37 Ni–Cu, 6,38,39 Pd–Cu, 7,40–42 Pt–Cu 43,44 and Zn–Cu 45–47 as extensively documented copper-based catalytic models. Choosing these models may help ensure that the combination of transition metals represented by Au, Ni, Pd, Pt and Zn demonstrates reliable catalytic activity when paired with copper.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Herein, the bimetallic alloy model was constructed by substituting the copper atoms with other transition metal (TM) atoms (Au, Ni, Pd, Pt and Zn). The primary rationale for selecting TM atoms was based on a literature review, which identified Au–Cu, 4,36,37 Ni–Cu, 6,38,39 Pd–Cu, 7,40–42 Pt–Cu 43,44 and Zn–Cu 45–47 as extensively documented copper-based catalytic models. Choosing these models may help ensure that the combination of transition metals represented by Au, Ni, Pd, Pt and Zn demonstrates reliable catalytic activity when paired with copper.…”
Section: Computational Detailsmentioning
confidence: 99%